Genetic Regulation of Vessel Morphology in Populus - Rodriguez-Zaccaro, F. Daniela; Henry, Isabelle M.; Groover, Andrew (Frontiers in Plant Science, 2021)
During secondary growth, forest trees can modify the anatomy of the wood produced by the vascular cambium in response to environmental conditions. Notably, the trees of the model angiosperm genus, Populus, reduce the risk of cavitation and hydraulic failure under water stress by producing water-conducting vessel elements with narrow lumens, which are more numerous and more interconnected with each other. Here, we determined the genetic architecture of vessel traits affecting hydraulic physiology and resilience to water stress. Vessel traits were measured for clonally replicated genotypes of a unique P. deltoides x nigra population carrying genomically-defined insertions and deletions that create gene dosage variation. We found significant phenotypic variation for all traits measured (mean vessel diameter, height-corrected mean vessel diameter, vessel frequency, height-corrected vessel frequency, vessel grouping index, and mean vessel circularity), and that all traits were under genetic control and showed moderate heritability values, ranging from 0.32 to 0.53. Whole-genome scans of correlations between gene dosage and phenotypic traits identified quantitative trait loci for tree height, mean vessel diameter, height-corrected mean vessel diameter, height-corrected vessel frequency, and vessel grouping index. Our results demonstrate that vessel traits affecting hydraulic physiology are under genetic control, and both pleiotropic and trait-specific quantitative trait loci are found for these traits.